Darrel of the Blessed Isles - Bacheller, Irving, 1859-1950 (Salt Lake City, UT : Project Gutenberg, 2004)
"Darrel of the Blessed Isles" by Irving Bacheller is a novel written in the early 20th century, reflecting themes of personal growth and the quest for identity amid life's challenges. The narrative follows a character named Sidney Trove, a boy of mysterious origins, who is raised by the Allens in a rural, simplistic life. As he grows, Trove grapples with the enigmas of his identity, shaped by his early experiences, the kindness of those around him, and his aspirations for a brighter future. The opening of the novel introduces Sidney Trove, who is discovered as a small child in a red sleigh by Theron Allen and his wife, amidst a snowbound landscape. Trove's arrival is mystifying; he speaks an unfamiliar language, showcasing his unknown origins. As he integrates into the Allen family, he quickly adapts to his new life, eventually thriving physically and intellectually. As the chapters unfold, they establish a rich backdrop of rural life, characterized by hard work, nature, and the steadfast morals of the characters, while hinting at the adventures and growth that await Trove on his journey toward self-discovery. The narrative ultimately invites readers to explore themes of belonging, the power of kindness, and the impact of personal choices in shaping one's destiny. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by Al Haines
Keywords: Fiction